Analisis Penerimaan Media Pembelajaran Mobile Based Augmented Reality Menggunakan Technology Acceptance Model terhadap Mahasiswa Teknik Elektro - Riyadhil Fajri; Mukhlidi Muskhir (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
This study aims to analyze student acceptance of the use of mobile-based learning media and augmented reality (AR) in the Electrical Circuit course at the Electrical Engineering Study Program at Padang State University. Using a mixed method approach, this research combines quantitative techniques through the Technology Acceptance Model (TAM) and qualitative approaches to explore student experiences through interviews. The results show that students' perceptions of ease of use (PEOU) have a significant effect on perceived usefulness (PU), which then affects attitudes towards use (ATU) and acceptance (ACC) of AR learning media. However, the relationship between PEOU and ATU, as well as PU and ATU, is not significant, indicating that affective aspects still need attention to increase positive attitudes towards the technology. Based on these findings, it is recommended that learning media developers pay attention to the user experience dimension and involve social factors and support in learning so that technology acceptance can be optimized. In conclusion, the successful integration of AR technology in education depends not only on convenience and usability, but also on emotional and social experiences that can support a more thorough learning process.